Specific antisense oligonucleotide composition & method for treatment of disorders associated with bronchoconstriction and lung inflammation - Nyce, Jonathan W. (My University, 2000)
A DNA comprises an oligonucleotide antisense to mRNA encoding an adenosine A.sub.1 or A.sub.3 receptor. The oligo is provided as a composition, various formulations, a capsule, and cartridge and in the form of a kit. The oligonucleotide of the invention is effective for reducing bronchoconstriction and/or allergy, and may be administered to a subject to treat respiratory ailments such as asthma and other conditions associated with the expression of adenosine receptors.